Neuromuscular and judo-specific tests: Can they predict judo athletes` ranking performance? - Lima Kons, R.; Franchini, E.; Detanico, D. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2020)
Background. The contribution of physical performance to the ranking list position of athletes would provide indications about the importance of monitoring their physical conditioning through neuromuscular and judo-specific tests. Problem and aim: verify if neuromuscular and judo-specific performance may predict the ranking list position of state-level judo athletes. Methods. Seventeen judo athletes participated in the study and were divided into two groups according to their state-level ranking position: top 20° (n=8) and positions 21°-38° (n=9). The athletes performed neuromuscular (shoulder external (PTEX) and inter-nal (PTINT) rotation torque, handgrip strength (HGS), vertical jumps (VJs) and judo-specific tests (Uchikomi Fitness Test (UFT), Special Judo Fitness Test (SJFT) and Judogi Grip Strength Dynamic (JGSTDIN) and Isometric Test (JGSTISO). T-test and multiple linear regression were used with the level of significance set at 0.05. Results. The main results demonstrated significant differences for most neuromuscular and judo-specific tests (p < 0.050), higher in the top 20° group than in the 21°-38° group. The SJFTTT, JGSTDIN and PTINT explained 88% of the variance in ranking position (p < 0.001). Conclusion. Neuromuscular performance (in most tests) in the upper and lower limbs and judo-specific assessments (JGSTDIN, SJFT total throws, and best series of UFT) differentiated the judo ranking position. In addition, the upper-body strength parame-ters (PTINT and JGSTDIN) and anaerobic capacity (SJFT total throws) were the variables that better explained the ranking position.